Experimental Determination of an Optimal Performance Map of a Steam Ejector Refrigeration System - Kittiwoot Sutthivirode; Tongchana Thongtip (Energies, 2022)
An experimental determination of optimal performance of a steam ejector refrigerator was proposed which aims to indicate the optimal performance under various heat source temperatures. A small-scale steam ejector refrigerator test bench was constructed to carry out the experiment and to determine the optimal performance map. Three primary nozzles with throat diameters of 1.4, 1.6, and 1.8 mm, were tested with an ejector throat diameter of 14.5 mm, providing the ejector area ratios of 107, 82, and 65, respectively. For a particular working condition, the boiler temperature was varied to determine the maximum COP which is recognized as the optimal operation. It was found that the secondary fluid stream is first choked at the optimal boiler temperature. This optimal point varied significantly with the evaporator temperature, condenser pressure, and ejector area ratios. It was found that this steam ejector refrigerator could be operated under the optimal boiler temperature between 102.5 and 117.5 °C depending on the ejector area ratio, evaporator temperature, and condenser pressure. The optimal performance map is beneficial to further control the heat source temperature so that the maximum COP is achieved.